British Christians and the Third Reich : church, state, and the judgement of nations - Chandler, Andrew (Cambridge, United Kingdom ; New York, NY, USA : Cambridge University Press, 2022)
"In this ground-breaking study, Andrew Chandler examines the complex relationship between religions and politics, church and state, and national and international politics during the period that witnessed the rise and fall of the Third Reich. He explores these dilemmas within the context of the tumultuous years when many British Christian confronted and challenged the Nazi regime. Chandler shows how many of the key moral questions which came to define the modern world now crystallized: What view should the Christian take of the political state? How should the claims of dictators and democrats be judged? How should the Church protest against injustice -- and what can be done about it? How should peace be preserved and when should war be declared? How should a just war be justly fought? It is a history which places the Third Reich firmly in an international perspective, revealing the moral arguments and debates that Nazism provoked across the democracies. It is also an important study of the many ways in which men and women outside Germany intervened, protested, and campaigned against the Hitler regime and sought to support its critics and its victims"--
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: Christianity and politics -- History -- 20th century; Church and state -- History -- 20th century; Christians -- Great Britain -- History -- 20th century; Germany -- History -- 1933-1945.